Karakteristik Turbin Angin Savonius Tiga Sirip Tipe Z Dengan Variasi Sudut Deflektor - Baso Alauddin; Aslim Muda Azis (Journal Teknik Dan Teknologi, 2024)
The purpose of the research is the Savonius type Z wind turbine equipped with a deflector to obtain the effect of the deflector angle on the torque, power and efficiency of the turbine. This study used an experiment on a prototype of a Savonius wind turbine type Z equipped with a deflector and used a wind tunnel with a variation in the number of blades of 30º, 45º, and 60º. The research was conducted with a constant wind speed of 5.33 m/s. Maximum torque of 0.47 Nm, and rotation of 0 rpm, with a load of 16 kg, deflector angle of 60º. While the maximum power is 0.98 Watts, at 35.4 rpm, with a load of 9 kg, deflector angle 60º. And Maximum efficiency of 14.10 %, at 35.4 rpm revolution, with a load of 9 kg, at a deflector angle of 60º.